Previously asymptomatic ruptured tubal ectopic pregnancy at over 10 weeks' gestation: Two case reports - Caitlin Gauvin; Melissa Amberger; Kevin Louie; Olga Argeros (Elsevier, 2019)
Ectopic pregnancy is a life-threatening condition affecting up to 2% of gestations. Implantation in the fallopian tube is most common, with symptoms typically presenting earlier for gestations in the ampulla and isthmus compared with the cornua and non-tubal sites. In this paper, the cases are described of two patients with advanced ectopic pregnancies that ruptured. One woman aged 36 years presented at 17 1/7 weeks' gestation with a ruptured cornual ectopic pregnancy. The other woman, aged 35 years, presented at 11 1/7' weeks gestation with a ruptured ectopic pregnancy in the left tubal ampulla. To our knowledge, there are no other reported cases of a tubal ampulla pregnancy presenting at such an advanced gestation with no prior symptoms. Keywords: Ectopic pregnancy, Rupture, Risk factors, Gestational age